Oncolytic Virotherapy: From Bench to Bedside - Yang, Ludi; Gu, Xiang; Yu, Jie; Ge, Shengfang; Fan, Xianqun (Frontiers in Cell and Developmental Biology, 2021)
Oncolytic viruses are naturally occurring or genetically engineered viruses that can replicate preferentially in tumor cells and inhibit tumor growth. These viruses have been considered an effective anticancer strategy in recent years. They mainly function by direct oncolysis, inducing an anticancer immune response and expressing exogenous effector genes. Their multifunctional characteristics indicate good application prospects as cancer therapeutics, especially in combination with other therapies, such as radiotherapy, chemotherapy and immunotherapy. Therefore, it is necessary to comprehensively understand the utility of oncolytic viruses in cancer therapeutics. Here, we review the characteristics, antitumor mechanisms, clinical applications, deficiencies and associated solutions, and future prospects of oncolytic viruses.